2019
DOI: 10.1016/j.jneumeth.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Studies on long term behavioural changes in group-housed rat models of brain and spinal cord injury using an automated home cage recording system

Abstract: long term behavioural changes in group-housed rat models of brain and spinal cord injury using an automated home cage recording system',

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…number of animals in the cage, healthy or injured together, both sexes together). Versatile examination of species‐specific behavioural changes and developing ethograms of animals in their home cages might be one future direction for translational research (Mogil, 2009 ; Yip et al., 2019 ). Clinically relevant behaviours related to a given aetiology of pain should also be studied.…”
Section: Translational Pain Researchmentioning
confidence: 99%
“…number of animals in the cage, healthy or injured together, both sexes together). Versatile examination of species‐specific behavioural changes and developing ethograms of animals in their home cages might be one future direction for translational research (Mogil, 2009 ; Yip et al., 2019 ). Clinically relevant behaviours related to a given aetiology of pain should also be studied.…”
Section: Translational Pain Researchmentioning
confidence: 99%
“…Recent developments in preclinical animal studies have suggested a more accessible alternative of investigating the impact of brain injuries using non invasive and continuous monitoring of individual behavioural changes in grouped housed animal cohorts whilst in their home cages [ 19 ]. Data obtained from such home cage automated (HCA) monitored behaviour provides large and comprehensive activity and physiological individual data from grouped housed animals, overcoming the constraints towards CNNs imposed by imaging modalities and therefore allows for more flexibility in data processing and model architecture.…”
Section: Introductionmentioning
confidence: 99%